Introduction to space sciences and spacecraft applications - Campbell, Bruce A., 1955-; McCandless, Samuel Walter (Houston, Tex. : Gulf Pub., 1996)
Introduction to Space Sciences and Spacecraft Applications.
Introduction and history -- Orbital principles -- Propulsion -- Spacecraft environment -- Communications -- Remote sensing -- Satellite navigation -- Spacecraft systems -- Spacecraft design.
Includes bibliographical references and index.
Keywords: Astronautics; Space vehicles; Electronic books